Constraints and Strategies in Scaling up of Innovations in Agricultural Extension: Insights from Telangana and Andhra Pradesh, India - , Nalla Anusha Reddy, K. Madhu Babu, B. Savitha, K. Suhasini, D. Srinivasa Chary (Archives of Current Research International, 2025)
Agricultural extension innovations are being adopted to tackle local challenges and enhance service delivery to farmers in terms of reach, efficiency, and relevance. Yet, their widespread scaling continues to face barriers due to systemic and contextual limitations. This study aimed to identify key constraints and propose tailored strategies for scaling up four major innovations: Farmer-Led Seed Production System (FLSPS), Saagu Baagu: E-MIRCHA, Rythu Seva Kendras (RSK), and Andhra Pradesh Community Managed Natural Farming (APCNF). The study was conducted in purposively selected districts across Andhra Pradesh and Telangana, covering 320 stakeholders i.e., 80 per innovation system representing Government agencies, NGOs, farmer organizations, and grassroots actors. Using the Garrett ranking technique, constraints were analyzed and prioritized. Results revealed that in FLSPS, lack of certified quality labs and limited storage and drying infrastructure were top-ranked issues. E-MIRCHA faced major barriers in terms of weak digital infrastructure and low digital literacy among farmers. For RSK, political interference and inadequate staff capacity were key impediments. In APCNF, delayed input supply and weak scientific validation emerged as the top challenges. These findings reflect broader concerns across innovation systems, including governance gaps, poor market access, limited financial support, and weak integration with existing institutional frameworks. Based on these insights, context-specific strategies were suggested—such as decentralized governance, performance-linked incentives for staff, public-private partnerships for infrastructure and technology, localized digital tools, and convergence with existing rural development schemes like NRLM and MGNREGS. The study concludes that sustainable scaling requires adaptive models grounded in institutional integration, continuous capacity building, and stronger farmer-centric data systems. Generating robust evidence, securing political and financial support, and integrating innovations into existing socio-political systems are key to ensuring their long-term impact and scalability in India’s diverse agricultural context.